2000
DOI: 10.1258/0956462001916001
|View full text |Cite
|
Sign up to set email alerts
|

Silent oophoritis due to cytomegalovirus in a patient with advanced HIV disease

Abstract: A case of isolated necrotizing cytomegalovirus (CMV) oophoritis disclosed only by necropsy studies in a patient with AIDS, is described. This unusual case report is discussed with a review of the literature dealing with CMV involvement of genital organs in the immunocompromised host, and in patients with HIV infection and AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
(19 reference statements)
2
12
0
Order By: Relevance
“…Originally described by Subietas et al in 1977 [ 8 ], bilateral CMV oophoritis is a rare pathologic finding that is usually associated with a systemic infection. An underlying malignancy or immunosuppressive status is almost always present and steroid therapy has been shown to be a strong risk factor for CMV reactivation in both groups [ 5 , 8 , 11 ], as it is in our current case. It has been suggested that previously reported isolated CMV oophoritis might represent sampling error [ 7 ].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Originally described by Subietas et al in 1977 [ 8 ], bilateral CMV oophoritis is a rare pathologic finding that is usually associated with a systemic infection. An underlying malignancy or immunosuppressive status is almost always present and steroid therapy has been shown to be a strong risk factor for CMV reactivation in both groups [ 5 , 8 , 11 ], as it is in our current case. It has been suggested that previously reported isolated CMV oophoritis might represent sampling error [ 7 ].…”
Section: Discussionsupporting
confidence: 65%
“…In fact, the lack of microthrombi was noted by Subietas et al [ 8 ] and actually considered one of the arguments against a virally induced vasculopathy. However, our case provides evidence for an alternate pathway for perpetuation of CMV infection in the ovary that does not require post menopausal restrictive vascular changes, thus providing one possible explanation for the nearly equal distribution between pre- and post- menopausal patients [ 1 - 3 , 5 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…All cases had associated immunosuppression: five cases (27.7%) were related to hematological malignancies 3 , 7 - 9 , 17 ; one (5.5%) was associated with glial neoplas 3 ; five (27.7%) was associated with carcinomas 3 , 10 , 12 , 15 , 16 ; one (5.5%) was associated with lupus glomerulonephritis 6 ; and six (33.6%; including the present report) were associated with AIDS. 2 , 4 , 11 , 13 , 14 In one case, CMV ovarian infection affected a fibrothecoma, which was present in one of the ovaries of a patient with refractory angioimmunoblastic non-Hodgkin lymphoma. 7 Fourteen of the 18 cases (77.7%) presented pre-mortem and post-mortem documentation of systemic involvement by CMV; 50% had an association with other opportunistic disease; and three cases (16.6%) received the treatment with ganciclovir.…”
Section: Discussionmentioning
confidence: 99%